CRIMINAL SANCTIONS FOR PARTICIPATION IN ACTS OF VIOLENCE LEADING TO MURDER IN ISLAMIC CRIMINAL LAW: A Case Analysis of Verdict No. 170/Pid.B/2021/PN.Pwk - Septiani, Nabila; Azazy, Yusup; Najmudin, Deden (Universitas Islam Madura, 2025)
The concept of participating in a criminal act refers to the involvement of several parties in committing a crime, either directly or indirectly, such as through incitement, orders, assistance, or due to negligence. In Islamic criminal law, this act is classified as jarimah which is contrary to the principle of Maqāṣid al-Syarī'ah. The sanctions imposed can be qiṣāṣ (appropriate retribution) or diyāt (fine). This study aims to examine the basis of judges' legal considerations in imposing criminal penalties in cases of participating in premeditated murder, focusing on Decision Number 170/Pid.B/2021/PN.Pwk. The method used is normative juridical research with a descriptive-analytical approach, using primary and secondary data. The results of the analysis showed that the defendant Rasta was legally and convincingly proven to have participated in the murder of the victim Fransisco Tamalu, so he was charged with Article 338 of the Criminal Code in conjunction with Article 55 paragraph (1) 1 of the Criminal Code. The panel of judges considered juridical and non-juridical aspects, as well as evidence in the form of witness statements, letters, and confessions of the defendant. The implications of this study show the importance of harmonization between Indonesian positive law and Islamic criminal law principles, especially in dealing with the involvement of other parties in criminal acts. This research can be a reference for judges, academics, and policymakers in developing a more fair and substantive justice approach to punishment.